2022
DOI: 10.1161/circresaha.122.320991
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Exposure, Blood DNA Methylation, and Cardiovascular Disease

Abstract: Background: Epigenetic dysregulation has been proposed as a key mechanism for arsenic-related cardiovascular disease (CVD). We evaluated differentially methylated positions (DMPs) as potential mediators on the association between arsenic and CVD. Methods: Blood DNA methylation was measured in 2321 participants (mean age 56.2, 58.6% women) of the Strong Heart Study, a prospective cohort of American Indians. Urinary arsenic species were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 112 publications
0
14
0
Order By: Relevance
“…Arsenic-associated DMCs at 20 and 13 CpGs were associated with CVD incidence and mortality, respectively. Functional models of arsenic-induced atherosclerosis also support the hypothesis that diabetes and redox signalling are involved in its pathogenesis [ 281 ]. Arsenic exposure also leads to phenotypic DNAm clock age acceleration [ 282 ].…”
Section: The Environmental Influence On Epigenomementioning
confidence: 77%
See 1 more Smart Citation
“…Arsenic-associated DMCs at 20 and 13 CpGs were associated with CVD incidence and mortality, respectively. Functional models of arsenic-induced atherosclerosis also support the hypothesis that diabetes and redox signalling are involved in its pathogenesis [ 281 ]. Arsenic exposure also leads to phenotypic DNAm clock age acceleration [ 282 ].…”
Section: The Environmental Influence On Epigenomementioning
confidence: 77%
“…Arsenic exposure at low exposure levels in water and food is related to multiple health outcomes, including cardiovascular disease (CVD) and hypertension [ 281 ]. It can also induce epigenetic modifications in experimental exposure models.…”
Section: The Environmental Influence On Epigenomementioning
confidence: 99%
“…Arsenic is a known epigenetic modulator resulting in DNA methylation, histone modifications, and microRNA changes (41). For instance, Domingo-Relloso et al reported a consortium of genomic positions differentially methylated by arsenic exposure in human blood from the Strong Heart Study cohort that associated with cardiovascular disease and a proportion of these genes were also significantly altered in mouse model of atherosclerosis as a result of arsenic exposure (42). We discovered that several genes in the differentially altered cistopics, such as Col1a1, Tgfbr1, and Nav2, etc., in our scATAC-Seq data corresponded to differentially methylated genes that correlated with arsenic exposure in this human dataset.…”
Section: Discussionmentioning
confidence: 99%
“…For example, arsenic-associated blood biomarkers based on DNA methylation can also explain part of the association between arsenic and CVD. 36 These epigenomic results of metals can further explain the overlap between environmental factors and precision cardiology, thus informing clinical decisions.…”
Section: Mechanisms Of Heavy Metal–induced Cardiotoxicitymentioning
confidence: 99%
“…Toxic heavy metals have epigenomic effects that include effects on DNA methylation and histone modification that can influence gene expression and downstream transcription. 36,140 Epigenetic modifications caused by heavy metals like lead and cadmium may be attributed to their ability to replace zinc, an essential element of various enzymes involved in epigenetic regulation. 141 It has also been reported that Cr (VI) can induce DNA damage and might activate or silence the expression of critical genes, 112 thus altering DNA methylation levels as well as global and gene-specific histone posttranslational modifications.…”
Section: Epigenomic Effectsmentioning
confidence: 99%